2019
DOI: 10.1016/j.brs.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous spinal direct current stimulation improves locomotor learning in healthy humans

Abstract: Background: Ambulation is an essential aspect of daily living and is often impaired after brain and spinal cord injuries. Despite the implementation of standard neurorehabilitative care, locomotor recovery is often incomplete. Objective: In this randomized, sham-controlled, double-blind, parallel design study, we aimed to determine if anodal transcutaneous spinal direct current stimulation (anodal tsDCS) could improve training effects on locomotion compared to sham (sham tsDCS) in healthy subjects. Methods: 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…Past studies with direct current stimulation applied over the scalp suggest that anodal stimulation enhances the rate and retention of learned motor task ( Nitsche and Paulus, 2000 ; Reis et al , 2009 ; Fritsch et al , 2010 ; Kadosh et al , 2010 ; Dayan et al , 2013 ; Snowball et al , 2013 ). Likewise, a recent study from our group, albeit in young and neurologically intact individuals, demonstrated that anodal tsDCS over the thoracolumbar vertebra enhanced the acquisition rate and retention of the trained locomotor task ( Awosika et al , 2019 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Past studies with direct current stimulation applied over the scalp suggest that anodal stimulation enhances the rate and retention of learned motor task ( Nitsche and Paulus, 2000 ; Reis et al , 2009 ; Fritsch et al , 2010 ; Kadosh et al , 2010 ; Dayan et al , 2013 ; Snowball et al , 2013 ). Likewise, a recent study from our group, albeit in young and neurologically intact individuals, demonstrated that anodal tsDCS over the thoracolumbar vertebra enhanced the acquisition rate and retention of the trained locomotor task ( Awosika et al , 2019 ).…”
Section: Discussionmentioning
confidence: 69%
“…Herein, we propose two potential explanations for this unexpected finding. Firstly, while anodal tsDCS at the spinal segmental level is understood to be facilitatory ( Winkler et al , 2010 ; Lamy et al , 2012 ; Awosika et al , 2019 ), its influence on ascending somatosensory pathways has been reported as inhibitory ( Cogiamanian et al , 2008 ; Truini et al , 2011 ; Lenoir et al , 2018 ), resulting in a phenomenon known as ‘anodal block’ ( Bhadra and Kilgore, 2004 ; Cogiamanian et al , 2012 ). Therefore, one possible explanation for our findings was that anodal tsDCS, in stroke patients, resulted in the inhibition of ascending sensory axons of the somatosensory pathway, which may have diminished the degree of proprioceptive feedback reaching supraspinal locomotor centres during BLTT ( Hao and Chen, 2011 ; Takakusaki, 2013 ; Clark et al , 2014 ; El-Basatiny and Abdel-Aziem, 2015 ; Schweizer et al , 2017 ; Takakusaki, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a novel and exciting mechanism of action has been recently proposed by Samaddar and co-workers [353]: they found that tsDCS also modulates the migration and proliferation of adult newly born spinal cells in mice, a cell population implicated in learning and memory; although the mechanisms are not fully understood, these findings suggest that tsDCS could be used, also in humans, as an early treatment to improve motor recovery in spinal cord lesions. In this connection, another study has confirmed that tsDCS increases locomotor skill acquisition and retention in healthy volunteers [354].…”
Section: Tsdcs On Clinical Applicationsmentioning
confidence: 93%
“…During the sham-TESS session, the electrodes were located in the same position, and the intensity of stimulation was set as the same intensity as used in TESS sessions and gradually decreased down to 0 in ϳ1 min. Similar sham stimulation procedures have been used successfully in previous neuromodulation studies using TESS to provide the initial sensation of stimulation without the subsequent effects (Murray et al, 2018;Awosika et al, 2019). During TESS without 5 kHz carrier frequency (tested on subjects listed as 1-8 on Table 1), single biphasic pulses (200 s duration) were delivered at a 30 Hz frequency (every 33.1 ms) for 20 min using the same intensity as described above.…”
Section: Methodsmentioning
confidence: 99%